RESTORATIVE JUSTICE: A NEW APPROACH TO RESOLVING DOMESTIC VIOLENCE - Jidatul Haz, M. Aaz; Wathoni, Lalu Muhammad Nurul; Zulkarnain, Zulkarnain; Maghfurrahman, Muhammad; Baldan Haramain, Fathur (Institut Agama Islam Negeri Bone, 2024)
Domestic Violence (a.k.a KDRT) has been identified as a form of crime that falls into the category of